2022
DOI: 10.3389/fsoc.2022.802090
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of self-efficacy on career aspiration and organizational support with subjective career success among Malaysian women managers during the Covid-19 pandemic

Abstract: The lives and jobs of many people have been negatively affected by the Covid-19 pandemic. Lockdowns to curb the pandemic have resulted in many people having to work from home. The question that arises is whether women's jobs are more vulnerable to the crisis. In this regard, it would be useful to understand the factors that affect career success, specifically that of Malaysian women managers. The present study sought to examine the impact of career aspiration and organizational support on subjective career suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…Thus, confirming that MSE mediates the effect of OCB on IB. This finding is consistent with that of prior researchers (Uppathampracha & Liu, 2022;Hamzah et al 2022;and Liao et al 2022) that found that SE mediates several organizational relationships. Thus, when marketers perceive that they have a high level of SE, they are more likely to exhibit citizenship and innovative behaviors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, confirming that MSE mediates the effect of OCB on IB. This finding is consistent with that of prior researchers (Uppathampracha & Liu, 2022;Hamzah et al 2022;and Liao et al 2022) that found that SE mediates several organizational relationships. Thus, when marketers perceive that they have a high level of SE, they are more likely to exhibit citizenship and innovative behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…The findings from SEM analysis revealed that SE mediated the relationship between ethical leadership and IB. Hamzah, Musa and Mohamad (2022) investigated the impact of career aspiration and organizational support on subjective career success, as well as the mediating role of SE in these relationships among 146 Malaysian women managers. Multiple linear regression analysis revealed a favorable correlation between subjective career success and high levels of aspiration for a career and perceived organizational support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adding credence to the claim stated by Ahmad et al (2019) that positive mental attitude and perseverance increase the odds of success in accomplishing one’s objectives. These results align with previous research (Blaique et al , 2022; Djourova et al , 2020; Hamzah et al , 2022), adding to the growing body of evidence that highlights the importance of resilience and determination in achieving career goals. This research has the potential to inform human resource departments on the views of today’s workers with regard to their own perception of success, as measured by CC, individual variances in resiliency and perceived levels of SE.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, SCS is influenced significantly by personal factors such as CC, CR and SE. This shift in perspective aligns with the changing landscape of modern careers, which increasingly emphasise self-fulfilment and personal growth as essential components of success (Hamzah et al, 2022;Rigotti et al, 2020;Schultheiss et al, 2023;Su et al, 2022). Second contributions of this study lie in the introduction of a serial mediation model.…”
Section: Theoretical Implicationsmentioning
confidence: 81%
See 1 more Smart Citation